1993
DOI: 10.1080/08985629300000021
|View full text |Cite
|
Sign up to set email alerts
|

Task role motivation and attributional style as predictors of entrepreneurial performance: female sample findings

Abstract: The main thrust of this study was directed at providing empirical evidence, at the g;ender level, for a predictive model of growth-oriented entrepreneurial performance. The model focuses on: (a) the relationship between role requirements of the entrepreneurial organization and five motivational patterns that fit these roles; (b) the mediating effect of the individual's ;~ttributional style for failure and success, and hislher perception of environmental uncertainty, o n two of the five motivational patterns. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 25 publications
0
12
0
2
Order By: Relevance
“…For example, a study by Masters and Meier (1988) found no significant difference in risk-taking propensity between men and women entrepreneurs. In fact, one study showed that women entrepreneurs and managers were actually more likely to take risks than their male counterparts, with the argument being that women actually have to be more willing to accept entrepreneurial risk because they face a more hostile and prejudicial work environment (Bellu, 1993). Subsequent research by Twenge (2001) found no differences in assertiveness based on the sex of the entrepreneur.…”
Section: Sex-based Stereotypes Within Entrepreneurshipmentioning
confidence: 99%
“…For example, a study by Masters and Meier (1988) found no significant difference in risk-taking propensity between men and women entrepreneurs. In fact, one study showed that women entrepreneurs and managers were actually more likely to take risks than their male counterparts, with the argument being that women actually have to be more willing to accept entrepreneurial risk because they face a more hostile and prejudicial work environment (Bellu, 1993). Subsequent research by Twenge (2001) found no differences in assertiveness based on the sex of the entrepreneur.…”
Section: Sex-based Stereotypes Within Entrepreneurshipmentioning
confidence: 99%
“…Others have sought for differences in entrepreneurial behaviour, defined by Chell et al (1991) as 'the striving for growth and renewal '. Miner (1993) and Bellu (1993) proposed five 'role requirements' together with five motivation patterns in their 'task role motivation theory'. And behind Smith's distinction between the 'craftsman entrepreneur' and the 'opportunistic entrepreneur' (1967) lies a complex of personality characteristics too.…”
Section: Entrepreneur-associated Factorsmentioning
confidence: 99%
“…Yet a rather sizable body of research has accumulated, lending considerable support to the early achievement motivation formulations (Bellu, 1988(Bellu, , 1993Bellu & Sherman, 1995;Miner, Smith, & Bracker, 1989Roberts, 1991). In addition there have been some rather positive reviews of the research on personality factors.…”
Section: Creating a Psychological Typologymentioning
confidence: 99%